2016
DOI: 10.1116/1.4971197
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the sticking coefficients of bis-diethyl aminosilane and trimethylaluminum in atomic layer deposition

Abstract: In this paper, the authors present the temperature dependent sticking coefficient (SC) of bis-diethyl aminosilane (BDEAS) and trimethylaluminum (TMA) in atomic layer deposition. SiO2 from BDEAS and ozone at substrate temperatures between 200 and 350 °C as well as Al2O3 from TMA and water deposited at substrate temperatures between 150 and 300 °C was deposited on our likewise in this journal published cavity test structures. The SC of BDEAS shows an Arrhenius dependence while for TMA no temperature dependent SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…3). Schwille et al 41 observed spikes in the saturation profile of TMA-water process measured with their MEMS-type conformality test structures by ellipsometry. They proposed that a CVD-related phenomenon might have contributed to the spikes.…”
Section: B Occasional Spikes In the Saturation Profilementioning
confidence: 99%
See 2 more Smart Citations
“…3). Schwille et al 41 observed spikes in the saturation profile of TMA-water process measured with their MEMS-type conformality test structures by ellipsometry. They proposed that a CVD-related phenomenon might have contributed to the spikes.…”
Section: B Occasional Spikes In the Saturation Profilementioning
confidence: 99%
“…We will refer to the structures by Gao et al 40 as PillarHall-1 (from PillarHallt, 1st generation). In turn, Schwille et al 30,41 fabricated centrosymmetric LHAR cavities resembling structures used in microelectromechanical systems (MEMS) processing; here, the limiting gap height was 4.5 mm. Recently, building upon the process of Gao et al, 40 improved microscopic rectangular LHAR channels have been developed and used, but not yet described in detail; 33,36,[42][43][44] describing them is among the goals of this work.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where r phs is the physisorption reaction rate, p i is the partial pressure of the species i, R is the ideal gas constant, T is the temperature, k b is the Boltzmann constant, m i is the molecular weight of species i, s c,i is the sticking coefficient of the species i at given temperature, N a is the Avogadro number, and σ is the average area per surface site. Although the sticking coefficient of BTBAS is not reported in previous works, we obtain its value through an analogy with the sticking coefficient of BDEAS because of structural and electronic similarity [60].…”
Section: Relative Rate Determinationmentioning
confidence: 99%
“…31 The sticking coefficient is the probability that an impinging precursor will react with a reactive site on the surface and has been reported for a few ALD processes. [32][33][34][35][36] Vertically aligned multiwalled carbon nanotube (MWCNT) forests offer an extreme high aspect ratio test structure for ALD. The ratio of forest height to the spacing between nanotubes can exceed 10,000.…”
Section: Introductionmentioning
confidence: 99%